Block, Natalia and Adams, Kathleen M. (eds.) (2023). Intersections of Tourism, Migration, and Exile - Levin, Adina (Documents d'Anàlisi Geogràfica, 2023)
Block, Natalia and Adams, Kathleen M. (eds.) (2023) Intersections of Tourism, Migration, and Exile Oxon and New York: Routledge ISBN 978-1-003-18268-9